2006
DOI: 10.1029/2006ja011759
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén wave filamentation and particle acceleration in solar wind and magnetosphere

Abstract: [1] We present numerical simulations of Alfvén waves in steady state, leading to the formation of intense magnetic filaments when the nonlinearity arises due to the ponderomotive effects and Joule heating. When the plain Alfvén wave is perturbed by a transverse perturbation and the magnitude of the pump Alfvén wave changes, chaotic filamentary structures of magnetic field in kinetic Alfvén wave (KAW) filamentation and quasiperiodic in inertial Alfvén wave (IAW) filamentation have been observed. At higher KAW p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Nonlinear effects associated with DAW so far studied by many authors [33][34][35][36] are limited to the situation when Joule heating and ponderomotive nonlinearities are considered. Recently Sharma et al 27 studied the nonlinear evolution of KAW/IAW when ponderomotive and Joule heating nonlinearities are introduced ͑by KAW/IWA in adiabatic case͒.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear effects associated with DAW so far studied by many authors [33][34][35][36] are limited to the situation when Joule heating and ponderomotive nonlinearities are considered. Recently Sharma et al 27 studied the nonlinear evolution of KAW/IAW when ponderomotive and Joule heating nonlinearities are introduced ͑by KAW/IWA in adiabatic case͒.…”
Section: Discussionmentioning
confidence: 99%
“…The above dynamical equation for KAW ͑IAW͒ has been studied by many authors numerically 23,26,27 and analytically [33][34][35][36] for the case when ‫ץ‬ x B y ӷ k 0x B y and ‫ץ‬ z B y Ӷ k 0z B y , where k 0x ͑k 0z ͒ is the component of the wave vector perpendicular ͑parallel͒ to ẑB 0 , but none of them has studied the filamentation of KAW ͑IAW͒ by coupling to MSW as presented in this manuscript.…”
Section: ͑11͒mentioning
confidence: 99%
“…Here, we have considered ∂ x B y Ӷ k 0x B y in writing (16). Taking the space as well as time dependence of the wave amplitude as ∼exp[i (k x x + αz − ωt)] and following the standard techniques [29], the system of (15) and (16) gives the following dispersion relation for low-β plasmas: (17) where B 0y is the pump DAW amplitude, k x and α are the perpendicular and parallel wave numbers of perturbation, respectively. The values of ζ 1 , ζ 2 and ζ 3 can be (b) Variation in growth rate temporal γ against k 0x λ e for low-β plasmas.…”
Section: Dispersive Alfvén Wave (Daw) Dynamicsmentioning
confidence: 99%
“…Growth rate and threshold power also calculated for modulational and filamentational instabilities. Many authors [16][17][18] studied the saturated spectra of KAW (IAW) and ion-acoustic turbulence by filamentation instability for adiabatic and non-adiabatic case. They found that the spectra approach the Kolmogorov k −5/3 scaling.…”
Section: Introductionmentioning
confidence: 99%
“…The above dynamical equation for DAW has been studied by many authors numerically 30,39,40 and analytically 31,32,41,42 by taking the appropriate value of n e in adiabatic and nonadiabatic cases, when the low-frequency perturbing wave is ion-acoustic wave. In our present case n e is due to the lowfrequency FW as given by Eq.…”
Section: ͑15͒mentioning
confidence: 99%